2022
DOI: 10.1029/2022gl099511
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Early Warning From Global Navigation Satellite System Data Using Convolutional Neural Networks

Abstract: Accurate tsunami early warning allows for more effective emergency planning, thereby mitigating the human and economic toll. However, constructing a rapid forecast model is challenging for several reasons. One is that the underlying physical processes are governed by partial differential equations whose solution requires substantial computation that cannot be performed in a short timeframe. Furthermore, determining the proper initial conditions for the differential equations requires solving the earthquake sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The Confusion Matrix showed that the model correctly classified 232 instances of potential tsunamis and 37 cases of non-potential tsunamis out of 269 actual occurrences. However, 52 instances were falsely International Journal Software Engineering and Computer Science (IJSECS), 4 (1) 2024, [13][14][15][16][17][18][19][20][21][22][23] Classification of Potential Tsunami Disaster Due to Earthquakes in Indonesia Based on Machine Learning predicted as non-potential tsunamis and 77 instances were falsely predicted as potential tsunamis, indicating some misclassifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Confusion Matrix showed that the model correctly classified 232 instances of potential tsunamis and 37 cases of non-potential tsunamis out of 269 actual occurrences. However, 52 instances were falsely International Journal Software Engineering and Computer Science (IJSECS), 4 (1) 2024, [13][14][15][16][17][18][19][20][21][22][23] Classification of Potential Tsunami Disaster Due to Earthquakes in Indonesia Based on Machine Learning predicted as non-potential tsunamis and 77 instances were falsely predicted as potential tsunamis, indicating some misclassifications.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the broader research landscape of improving tsunami predictions through machine learning techniques. Recent studies have explored the use of Convolutional Neural Networks for tsunami early warning systems [21], machine learning-based tsunami inundation prediction from offshore observations [22], and estimation of tsunami bore forces using Extreme Learning Machines [23]. These advances underscore the continuous efforts to leverage sophisticated algorithms and data sources to refine tsunami prediction models and effectively mitigate the impact of earthquake-generated tsunamis.…”
Section: Related Workmentioning
confidence: 99%
“…Núñez et al (2022) use convolutional neural networks to predict tsunami time series at specific locations. Rim et al (2022) also use convolutional neural networks to forecast tsunami waveforms from Global Navigation Satellite System (GNSS) data at selected locations. Finally, Mulia et al (2022) use MLP networks to predict flow depths in several coastal locations from offshore tsunami data at 150 offshore stations in the Japan Trench.…”
Section: Introductionmentioning
confidence: 99%
“…Rim et al. (2022) also use convolutional neural networks to forecast tsunami waveforms from Global Navigation Satellite System (GNSS) data at selected locations. Finally, Mulia et al.…”
Section: Introductionmentioning
confidence: 99%
“…Such an instability would limit their use in applications where stable and accurate prediction is critical. For example, NNbased tsunami early warning models (Makinoshima et al, 2021;Liu et al, 2021;Mulia et al, 2022;Rim et al, 2022) will need to be stable with respect to uncertainty in its input, as the real input measurement is subject to various measurement noise, sensor malfunctions, or other types of anomalies during a tsunamigenic earthquake event (Titov et al, 2005;Kumar and Ahmed, 2011). As NNs are known to produce erroneous predictions when there is a specific type of noise in the input data, analyzing and controlling these instabilities is of utmost importance in order to use them for safety-critical applications.…”
Section: Introductionmentioning
confidence: 99%